Ampliando futuros: o curso pré-vestibular comunitário da Maré - Silva, Elionalva Sousa (2006)
A study about the communitarian 'Pré-vestibular' Course of Maré (CPV-Maré), and of its insertion on the movement of communitarian ‘pré-vestibulares’, existing all over Brazil. The data and the sources collected brought the possibility of understanding how the trajectory of the course was achieved, as well as its results and limits. Through the development of the course, it is possible to understand the process of development and institutionalization of the 'Centro de Estudos e Ações Solidárias da Maré' (CEASM), a non-governmental organization, which was created by the residents and ex-residents of Maré in 1997 and whose development was expressive. In seven years of existence –1998 to 2005 –the students who attended the CPV-Maré obtained 539 approvals for public and private universities, mainly for the PUC-RJ, totalizing 408 entries of students in the higher education. In accordance with the proposal of the course and taking into account the economic condition of the students, only the approvals for public universities and for the PUC-RJ will be considered, due to the partnership between this university and the CEASM, with regard to the concession of scholarships. Therefore, there are 355 students who entered the public universities and the PUC-RJ. This study will work with this quantitative.